The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1021/jf303395q
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Composition of Oyster Leaf (Mertensia maritima (L.) Gray)

Abstract: Oyster leaf (Mertensia maritima), also called vegetarian oyster, has a surprising oyster-like aroma. Its volatile composition was investigated here for the first time. In total, 109 compounds were identified by gas chromatography-mass spectrometry (GC-MS) and quantified by GC-FID. The use of GC-olfactometry on both polar and nonpolar columns allowed the detection of the molecules having an oyster-like, marine odor. Four compounds were identified and confirmed by synthesis: (Z)-3-nonenal, (Z)-1,5-octadien-3-ol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…In the fresh S. ramosissima samples, two peaks of high intensity were identified, which corresponded to 3-hexen-1-ol (47.95%) and 1-hexanol (47.82%). Both alcohols are known to be responsible for green-type odors and 3-hexen-1-ol has also been described as a seaweed odor [ 50 , 51 ]. In addition, hexanal (0.26%), ethyl tiglate (1.51%), 3-hexen-1-ol acetate (0.33%), and methyl and ethyl benzoate (0.54% and 0.21%, respectively) are responsible for odors such as green, herbal, fruity, and floral [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the fresh S. ramosissima samples, two peaks of high intensity were identified, which corresponded to 3-hexen-1-ol (47.95%) and 1-hexanol (47.82%). Both alcohols are known to be responsible for green-type odors and 3-hexen-1-ol has also been described as a seaweed odor [ 50 , 51 ]. In addition, hexanal (0.26%), ethyl tiglate (1.51%), 3-hexen-1-ol acetate (0.33%), and methyl and ethyl benzoate (0.54% and 0.21%, respectively) are responsible for odors such as green, herbal, fruity, and floral [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…It inhabits shingle beaches, and rarely sandy beaches, and is difficult to cultivate in the garden because of stringent temperature requirements [11]. Mertensia maritima has been grown in Northern Scotland and Southwestern France for its fragrant leaves [12]. The oyster plant is naturally propagated through seeds, but germination is poor due to seed dormancy.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Skarpaas and Stabbetorp [13] reported that a cold period was essential to break seed dormancy and a cold treatment of oyster plant seeds at 2 °C was shown to enhance germination. The food reserve in M. maritima is fat [11] and the volatile composition of the oyster plant has been well-documented [12], with approximately 109 volatile compounds being identified from M. maritima leaf extracts. In addition, three main compounds, allantoin, rabdosiin, and rosmarinic acid, were isolated from callus extracts of M. maritima [14].…”
Section: Introductionmentioning
confidence: 99%
“…This technique, described in a number of publications, [2][3][4][5] with applications reported in the flavour, fragrance, and other domains, [6][7][8][9][10][11][12] can also be used to estimate the purity of chemically-defined flavouring substances or chromatographic standards using these predicted RRF.…”
Section: Introductionmentioning
confidence: 99%